2020
DOI: 10.3390/jcm9010119
|View full text |Cite
|
Sign up to set email alerts
|

World Health Organization’s Growth Reference Overestimates the Prevalence of Severe Malnutrition in Children with Sickle Cell Anemia in Africa

Abstract: Anthropometric indices are widely used to assess the health and nutritional status of children. We tested the hypothesis that the 2007 World Health Organization (WHO) reference for assessment of malnutrition in children with sickle cell anemia (SCA) overestimates the prevalence of severe malnutrition when compared to a previously constructed SCA-specific reference. We applied the WHO and SCA-specific references to children with SCA aged 5–12 years living in northern Nigeria (Primary Prevention of Stroke in Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 21 publications
0
12
0
1
Order By: Relevance
“…Programmes have been able to increase the uptake of skilled maternal health attendants and encourage the use of facility-based maternal and child health services, 82 reduce mother to child HIV transmission, 83 prevent strokes in children with sickle-cell disease, 84 , 85 and generally improve collaboration and promote uptake of evidence-based interventions. 86 , 87 , 88 …”
Section: Section 3: An Evolving Burden Of Disease Challenges a System...mentioning
confidence: 99%
See 1 more Smart Citation
“…Programmes have been able to increase the uptake of skilled maternal health attendants and encourage the use of facility-based maternal and child health services, 82 reduce mother to child HIV transmission, 83 prevent strokes in children with sickle-cell disease, 84 , 85 and generally improve collaboration and promote uptake of evidence-based interventions. 86 , 87 , 88 …”
Section: Section 3: An Evolving Burden Of Disease Challenges a System...mentioning
confidence: 99%
“…Programmes have been able to increase the uptake of skilled maternal health attendants and encourage the use of facility-based maternal and child health services, 82 reduce mother to child HIV transmission, 83 prevent strokes in children with sickle-cell disease, 84,85 and generally improve collaboration and promote uptake of evidence-based interventions. [86][87][88] Nonetheless, rates are well above the levels required to meet SDG 3•1 and 3•2 to substantially reduce maternal, neonatal, and child mortality. UN estimates of neonatal mortality in 2019 were of 36 per 1000 livebirths and GBD estimates of 49 per 1000 livebirths, both at levels far above the targets.…”
Section: Health Is Made Within Communities and At Home: Health Creati...mentioning
confidence: 99%
“…Our unanticipated finding suggests that BMI has no impact on the severity of anaemia. Similarly, our group recently reported that there was no significant association between severe malnutrition (using BMI) and low haemoglobin 31 …”
Section: Discussionmentioning
confidence: 64%
“…Similarly, our group recently reported that there was no significant association between severe malnutrition (using BMI) and low haemoglobin. 31 As expected with cross-sectional study design, our study has limitations. Due to its cross-sectional design, we were unable to ascertain the causes of severe anaemia and the clinical impact of severe anaemia on overall health, disease severity and mortality.…”
Section: Discussionmentioning
confidence: 77%
“…Portanto, os indivíduos em situação socioeconômica vulnerável merecem atenção especial no que diz respeito às perspectivas médica e psicossocial, visto estarem mais expostos aos fatores sociais determinantes da DF (Paiva e Silva et al, 1993). Essa condição é relatada por Ghafuri et al (2020) ao sinalizarem a necessidade de recursos para tratamento e gerenciamento da desnutrição em crianças nigerianas com AF. Assim, é possível inferir que a mesma necessidade pode ser atribuída às crianças brasileiras, visto que a desnutrição, apesar de cada vez menor, ainda é um problema social relevante no país.…”
Section: Resultsunclassified